Optimizing rabbit semen cryopreservation using different cryoprotectants in a Tris-based extender - Khalil, Wael A.; Fouda, Sara F.; El-Ratel, Ibrahim T.; El-Haroun, Ehab; Sindi, Ramya Ahmad; Moussa, Mahmoud; Abdelnour, Sameh A. (Frontiers in Veterinary Science, 2026)
This experiment investigates the potential effects of different cryoprotectant molecules, such as glycerol (GL) and dimethyl sulfoxide (DMSO), added to a Tris-based extender focusing on assessing sperm quality, antioxidant status, acrosome integrity, apoptosis, semen microbiota of post-thawed rabbit semen, and in vivo fertility trial in rabbit does. The Tris-based extender was supplemented with various cryoprotectants to form the following five experimental treatments: 4% DMSO (DM4), 4% DMSO+50 mM trehalose (DMTR), 4% DMSO+50 mM sucrose (DMSU), 4% glycerol (GL4), or a mixture of 2% DMSO + 2% glycerol (DMGL2). The results indicate that the DM4 group had better results for progressive motility, viability, and membrane integrity (p < 0.001). Sperm kinematic parameters were the greatest in all DMSO groups compared to the GL groups (p < 0.01). Fortified Tris with DMTR or DMSU significantly improved live sperm with intact acrosomes and significantly reduced live sperm with detached acrosomes (p < 0.01). DMTR group had the greatest total antioxidant capacity (TAC) and lowest malondialdehyde (MDA) and reactive oxygen species (ROS) levels compared to other groups (p < 0.01). Moreover, nitric oxide decreased in DMTR or DMSU groups compared to other groups (p < 0.05). Viable sperm was the greatest in DMSU group, while apoptotic (%) was the lowest in DMSU and DMTR groups (p < 0.01). Total bacterial count was higher in the DM4 group, while lowest in the DMSU group (p < 0.01). While the DMSU treatment resulted in the highest conception rate, no significant differences were observed in litter size across groups (p > 0.05). The cryo-tolerance of rabbit spermatozoa was significantly improved by modifying the freezing extender to include 4% DMSO enriched with either 50 mM Trehalose or 50 mM Sucrose. This optimized formulation enhanced post-thaw parameters, specifically leading to higher sperm kinematics (e.g., motility and velocity), preserved acrosome integrity, and a reduction in apoptosis-like changes. The mechanism for this protective effect is attributed to the synergistic action of DMSO and the disaccharides in mitigating oxidative stress by enhancing the activity of intrinsic antioxidant defenses within the spermatozoa.